Welfare Stigma in the Lab: Evidence of Social Signaling - Jana Friedrichsen; Tobias König; Renke Schmacker (Center for Economic Studies and ifo Institute (CESifo), 2017)
Using a laboratory experiment, we present first evidence that stigmatization through public exposure causally reduces the take-up of an individually beneficial transfer. Our design exogenously varies the informativeness of the take-up decision by varying whether transfer eligibility is based on ability or luck, and how the transfer is financed. We find that subjects avoid the inference both of being low-skilled and of being willing to live off others. Using a placebo treatment we can exclude other explanations for the observed stigma effect. In the experiment, social stigmatization implies a reduction in the take-up rate of 30 percentage points.
Keywords: D03; H31; I38; C91; 330; stigma; signaling; redistribution; non take-up; welfare program